2018
DOI: 10.1111/arcm.12446
|View full text |Cite
|
Sign up to set email alerts
|

The Supply of Glass at Portus Ilicitanus (Alicante, Spain): A Meta‐Analysis of HIMT Glasses

Abstract: Portus Ilicitanus (Picola, Alicante) was the main sea harbour of the Roman Colonia Iulia Ilici Augusta and as such played a crucial role in the supply of fundamental commodities to the Iberian Peninsula. Excavations yielded large quantities of glass in fourth‐ and early fifth‐century contexts. Elemental analysis of 60 samples by laser ablation – inductively coupled plasma – mass spectrometry (LA–ICP–MS) confirmed that the glasses were imported from the Eastern Mediterranean. A majority of the glasses correspon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…However, this import appears to relate only to isolated, finished objects and not to the trade of raw glass en masse. In contrast, raw glass chunks indicative of bulk imports and regional secondary working have been recovered from numerous late antique and Visigothic Iberian sites ( 11 , 26 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, this import appears to relate only to isolated, finished objects and not to the trade of raw glass en masse. In contrast, raw glass chunks indicative of bulk imports and regional secondary working have been recovered from numerous late antique and Visigothic Iberian sites ( 11 , 26 ).…”
Section: Resultsmentioning
confidence: 99%
“…The contents of Nb, Y, Zr, and TiO 2 have been compared in binary plots. The glasses of the subgroup 1A (HIMT1) show high contents of these elements in line with a sand batch that was rich in heavy minerals and/or clays (Figure 9) (Brems et al, 2018;De Juan Ares et al, 2019a;Freestone et al, 2002;Gliozzo et al, 2019). The samples US122-Y and US122-76, considered of doubtful attribution because of their low Na 2 O contents, show compositions in agreement with the other samples of the sub-group 1A, thereby confirming the hypothesis that these glasses were subjected to only by a superficial de-alkalinisation.…”
Section: Trace Element Concentrationsmentioning
confidence: 77%
“…The glasses of the subgroup 1B show chemical characteristics that can be related to the HIMT2 type. Bibliografic data from: Brems et al, 2018;Ceglia et al, 2015Ceglia et al, , 2019De Juan Ares et al, 2019a;Foy et al, 2003;Gliozzo et al, 2019;Phelps et al, 2016;Schibille et al, 2017Schibille et al, , 2019 Indeed, differing from the HIMT1 glasses, the samples show lower contents of FeO, TiO 2 and Mn. Furthermore, CaO and Al 2 O 3 contents vary around 7-8 wt% and 2.5-3 wt% respectively.…”
Section: Major Element Concentrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…About ten major compositional groups of Roman and late antique natron‐type glasses have by now been identified that can be traced back to different primary productions in the Levant and in Egypt [2–8] . Recent work on late antique and early medieval assemblages from Spain has established changing supply patterns of Egyptian and Levantine base glass types, an increase in recycling particularly in the seventh and eighth centuries, and the gradual development of a local primary glassmaking industry [9–11] . However, the distinction of the output of different secondary workshops that fabricated vessels from raw glass based on compositional features still proves challenging [1]…”
Section: Introductionmentioning
confidence: 99%